Graphical approach to minimum flowrate targeting for partitioning water pretreatment units - Tan, Raymond Girard R. (Animo Repository, 2010)
Pretreatment is often necessary when the fresh water available to industrial plants is impure, and when some processes are particularly sensitive to contaminants. Partitioning processes such as membrane separation units are often used for such applications. However, the use of pretreatment units adds to capital and operating costs for a water system. Hence, it is of interest to develop design procedures to minimize the cost for such system. This work presents a graphical pinch analysis approach for targeting minimum flowrate of partitioning water pretreatment systems in single component problem. The approach determines how product and reject streams from the treatment unit can be allocated, along with bypassed freshwater, to satisfy multiple process sinks with their respective flowrate and purity requirements. Hypothetical case studies are presented to illustrate the approach, and generalized design principles based on pinch analysis heuristics are drawn from the examples. © 2009 The Institution of Chemical Engineers.